Lessons for pandemic management in rural healthcare settings in India: a retrospective cohort study of COVID-19 in a rural COVID care centre - R., Seetharam Mysore; M., Vidyashree; Shields, Sydney; Suryanarayana, Kumar Gavali; Kalliath, Priyanka Catherine Mani; Naik, Vishwesh Vishnu; Thambad, Mohan Kumar B.; Srinivasaiyer, Anantha Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: The COVID-19 pandemic has affected billions of lives across all countries precipitating an unprecedented demand for simultaneous curative, preventative, promotive, and curative services which has impacted the entire healthcare system. Even as it continues to rage across the globe, it is pertinent to learn from current experiences to build resilience into the system, especially for the vulnerable populations in rural areas. Methods: A retrospective cohort study of COVID-19 was conducted at COVID care centre in Vivekananda Memorial Hospital. A total of 136 COVID-19 confirmed patients were included in the study. Epidemiological and clinical profiles of patients were summarised. The association between risk factors and COVID-19 disease progression and patients’ outcomes at discharge were analysed and adjusted risk ratios were presented. Results: Out of the 136 patients, 128 were discharged uneventfully, 7 were referred to a higher centre because of disease progression and one patient died due to cardiac arrest. The study showed statistically significant association between age above 50 years and the presence of diabetes with COVID-19 disease progression. Delayed presentation for care also carried a higher risk of negative outcomes. Significant number of diabetics had derangement of their glycaemic control during the period of study. Conclusions: The study has highlighted the importance of ensuring essential non-COVID public health services, especially targeted follow-up of older adults, people with diabetes for their treatment adherence and early detection and treatment initiation of COVID-19 amongst them.